Anticipation of Emerging Disease Mycoplasma bovis: Prevention and Control - Faidah Rachmawati; Hastuti Handayani S Purba; Susan M Noor (Indonesian Center for Animal Research and Development, 2019)
Mycoplasma bovis is one of the pathogens, causes respiratory, reproductive, mastitis and arthritis disorders in cattle. Due to the economic impact of this disease, Mycoplasma bovis must be free on farms. There are no pathognomonic symptoms of Mycoplasma infection, so it needs laboratory confirmation to diagnose. Many countries have routinely examined M. bovis on cases of mastitis, arthritis, pneumonia and reproductive disorders. There was no cases of respiratory disorder in cattle related to M. bovis infection reported in Indonesia. The fact that, in many countries almost that cases related to the presence of M. bovis. The presence of M. bovis in Indonesia should be investigated, considering that Indonesia imports cattle from Australia and New Zealand that expose to M. bovis. This paper discusses the incidence of M. bovis infection in many countries including its economic impact, clinical symptoms, and method of diagnosis and control of disease to anticipate the emergence of this disease in Indonesia.